On the Performance of Trimetazidine and Vitamin E as Pharmacoprotection Agents in Cyclosporin A-Induced Toxicity. (9th April 2013) - Cristina, De la Cruz Rodríguez Lilia; del Rosario, Rey María; Carmen Rosa, Araujo; Ana Veronica, Oldano
Abstract : The immunosuppressant drug cyclosporin A (CyA) has been used in diseases with immunological basis and in transplant patients. Nephrotoxicity and hepatotoxicity are the main adverse effects of this drug. To find a protective drug against those effects we assayed the cardioprotector Trimetazidine (TMZ) and vitamin E, used as nutritional supplements to alleviate oxidative stress. Six groups of eight male Wistar rats each were prepared (groups A–F): A, control; B, vitamin E (10 mg/Kg/day); C, TMZ (20 mg/Kg/day); D, 25 mg/Kg/day CyA; E, CyA and vitamin E (25 mg/Kg/day CyA + 10 mg/Kg/day Vit E); F, TMZ for 20 days (20 mg/kg/day); and then CyA (25 mg/kg/day) and TMZ (20 mg/Kg/day). The experiment lasted 120 days. The exposure of rats to CyA promoted nephrotoxicity and hepatotoxicity with an increase in serum urea, creatinine, and glutamate dehydrogenase (GLDH). Structural and ultrastructural studies of liver and kidney were performed. Group D showed adverse effects induced by CyA since statistically significant differences were found with respect to the control group (A). Vitamin E (E) showed no protective effect. Pretreatment with TMZ (F) attenuated the adverse effects of CyA. We conclude that CyA-induced nephrotoxicity and hepatotoxicity are attenuated by the cytoprotective effect of TMZ. TMZ inhibits the reabsorption and, consequently, the accumulation of CyA in the cell. The antioxidant capacity of vitamin E did not improve the effect of CyA.